Structural innovation design of mobile chassis for inspection robots based on the TRIZ theory - WANG Zhihui; LI Kangkang; WANG Chengjun (Jixie chuandong)
ObjectiveAiming at the problem that the working plane of inspection robots equipped with precision instruments can’t always maintain stable when moving on complex road surfaces such as bosses and trenches, an innovative design of the robot’s mobile chassis structure was proposed based on the contradiction analysis method and the material field model.MethodsA floating structure design was proposed and obstacle crossing analysis and driving smoothness analysis under complex road conditions such as bosses and trenches were conducted on the floating mobile chassis. The comparative simulation of the original structure chassis and improved mobile chassis moving under complex road conditions was conducted in Admas simulation software. A floating mobile chassis test prototype was built to conduct motion tests under complex road conditions.ResultsThe test results indicate that the floating mobile chassis has strong adaptability, and the working plane can maintain stable when crossing obstacles.